2021
DOI: 10.3389/fmars.2020.596534
|View full text |Cite
|
Sign up to set email alerts
|

The hsp40 Gene Family in Japanese Flounder: Identification, Phylogenetic Relationships, Molecular Evolution Analysis, and Expression Patterns

Abstract: Heat shock proteins (hsps) are cellular chaperones that are involved in developmental stages and stress responses. Hsp40 is the major subfamily of hsps, but has not been fully characterized in Japanese flounder (Paralichthys olivaceus), especially their roles in immune response. In this study, a comprehensive identification and analysis of hsp40 in flounder is presented, including gene structures, evolutionary relationships, conserved domains, molecular evolution analysis, and expression patterns. Sequence fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 99 publications
1
2
0
Order By: Relevance
“…In another immune related study, Japanese flounder, Paralichthys olivaceus, showed 88% differential expression patterns of immune response gene after bacterial challenged (E. tarda), where the most abundance gene was known as the heat shock protein (hsp40) gene. This finding provides valuable evidence that hsp40 genes are responsible in participating in disease defense system of the fish (Yan et al, 2021). It has been reported from previous study that hsp protein played a role in humoral and cellular responses of innate immunity in aquatic organisms (Huang et al, 2018).…”
Section: Genomicssupporting
confidence: 60%
“…In another immune related study, Japanese flounder, Paralichthys olivaceus, showed 88% differential expression patterns of immune response gene after bacterial challenged (E. tarda), where the most abundance gene was known as the heat shock protein (hsp40) gene. This finding provides valuable evidence that hsp40 genes are responsible in participating in disease defense system of the fish (Yan et al, 2021). It has been reported from previous study that hsp protein played a role in humoral and cellular responses of innate immunity in aquatic organisms (Huang et al, 2018).…”
Section: Genomicssupporting
confidence: 60%
“…DNAJC10 and DNAJA1 belong to small molecule HSPs (HSP40s), which can bind to HSP70s through the J domain to enhance the interactions between HSP70s and substrates ( Qiu et al, 2006 ; Liu et al, 2020 ). HSP40s are involved in immune defense when the organism is stimulated ( Yan et al, 2021 ). Figure 8 shows that the genes of HSPs were significantly upregulated after 4 h of exposure to high temperature, while the genes of the HSPs were significantly downregulated after 24 h of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the R package (clusterProfiler 4.0) were utilized for enrichment analysis, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA) [ 69 , 70 , 71 ]. In our previous studies, genome-wide identification of hsp10/20/40/60 family members and their systematic bioinformatic analyses were performed; the expression profiles of the four subfamilies above and the hsp70 subfamily were analyzed according to our transcriptome data [ 72 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%